Using Authentic Assessment to Measure Basic English Speaking Skill of Students Majoring in Japanese Study - Lenggahing Asri Dwi Eko Saputri (KIRYOKU, 2021)
This study aims at describing the implementation of authentic assessment to measure Basic English speaking skill of students majoring in Japanese study. The description consists of three parts, namely designing the authentic assessment, implementing the authentic assessment and scoring students’ speaking skill. This study applies qualitative descriptive method. The data was collected through class observation. The result of the study revealed that authentic assessment was considered as the most effective way in assessing students’ performance in the classroom as its ability to assess the whole process of learning rather than just testing students’ knowledge at the end of the course. In conducting the authentic assessment to measure Basic English speaking skill of students majoring in Japanese study, the lecturer designed the authentic assessment based on the six steps suggested by Pierce and O’Malley (1996), implemented performance assessment to measure the students speaking skill and used analytic rubric in scoring the students speaking skill.